2015
DOI: 10.1016/j.eneco.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting day-ahead electricity prices: Utilizing hourly prices

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 28 publications
3
58
0
Order By: Relevance
“…A white square indicates that forecasts of a model on the X-axis are better for all 24 hours, while a black square that they are not better for a single hour. (2014), Raviv et al (2015), Gaillard et al (2016), Marcjasz et al (2018) and Nowotarski and Weron (2018), among others. In Table 4 we report the MAE values for the better of the two lasso models (this is in row 'Better of the two') and their arithmetic average (row 'Combination').…”
Section: The Standard Dm Test and The Performance Across The Hoursmentioning
confidence: 99%
See 1 more Smart Citation
“…A white square indicates that forecasts of a model on the X-axis are better for all 24 hours, while a black square that they are not better for a single hour. (2014), Raviv et al (2015), Gaillard et al (2016), Marcjasz et al (2018) and Nowotarski and Weron (2018), among others. In Table 4 we report the MAE values for the better of the two lasso models (this is in row 'Better of the two') and their arithmetic average (row 'Combination').…”
Section: The Standard Dm Test and The Performance Across The Hoursmentioning
confidence: 99%
“…Vector AutoRegression (VAR) is the basic modeling structure in the fully multivariate context, for sample EPF applications see Huisman et al (2007), Panagiotelis and Smith (2008), Haldrup et al (2010) and He et al (2015). However, if the number of parameters is very large it may be a good idea to reduce dimensionality of the problem first and consider factor models, as in Garcia-Martos et al (2012), Wu et al (2013), Weron (2015, 2016) and Raviv et al (2015). In one of the few applications in the computational intelligence EPF literature, Yamin et al (2004) use a neural network with 24 nodes in the output layer, hence consider a fully multivariate approach.…”
Section: The Multivariate Modeling Frameworkmentioning
confidence: 99%
“…More recently, but without accounting for fundamental drivers and looking only at point forecasts, Raviv et al (2015) compared the performances of models for the full panel of 24 hourly prices studying NordPool from 1992 to 2010. Based on univariate AR and multivariate VAR models, they computed forecast combinations and empirically demonstrated that the useful predictive information contained in disaggregated hourly prices improves the forecasts of multivariate models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is an aggregate that equals the average of hourly prices for delivery during each of the 24 hours. 12 The use of daily aggregated data in empirical studies has been often motivated by the need for the most parsimonious model relating prices' characteristics such as spikes occurrence and extreme volatility to a limited number of exogenous factors. Relying on daily data simplifies assessing the seasonal components and the influence of many important driving factors.…”
Section: Previous Researchmentioning
confidence: 99%